Significant aspects in the trainingprocess ofEducators for Inclusion and Internationalization - Dugois, Rosana Cristina Miranda; Schlunzen, Klaus Junior [UNESP]; Schlunzen, Elisa Tomoe Moriya (Univ Nove Julho, 2023)
: This article refers to a dialogue between the authors' experiences with the literature on scientific research, production, knowledge, internationalization of classical researchers and substantial productions to carry out critical and analytical reflection in a context with research in education. Specifically, in teacher training processes, their fields of research, inclusion and internationalization. The objective of this article is to reflect, conceptualize and analyze the importance and development of research on teacher training processes, public policy managers in education, international agendas and interculturality for inclusion. The work adopts a qualitative approach with a focus on the interpretation of social, cultural and human phenomena, its methodology is bibliographical research, translating into discussion of aspects that lead to the need for revisions and implementations related to scientific research in education, internationalization and inclusion for educational policies.
Keywords: teacher training; internationalization; scientific research in education; public policies in education